Aortic Arch Calcification Predicts the Renal Function Progression in Patients with Stage 3 to 5 Chronic Kidney Disease. (28th January 2015) - Li, Lung-Chih; Lee, Yueh-Ting; Lee, Yi-Wei; Chou, Chia-An; Lee, Chien-Te
Abstract : Introduction . The presence of aortic arch calcification (AoAC) and cardiomegaly on chest radiography has been demonstrated as important risk factors for cardiovascular mortality in patients with chronic kidney disease (CKD). However, the interrelationship among AoAC, cardiomegaly, and renal function progression remains unclear. The aim of this study is to assess whether AoAC and cardiomegaly are independently associated with the renal function progression in patients with stages 3–5 CKD. Methods . We retrospectively determined AoAC and cardiomegaly by chest X-ray in 237 patients, followed up for at least three years without entering dialysis and classified into 4 groups according to the presence or absence of AoAC and cardiomegaly. The change in renal function was measured by the slope of estimated glomerular filtration rate (eGFR). Results . Of the 237 patients, the rate of eGFR decline was significantly higher in the group with coexistence of AoAC and cardiomegaly than any other groups. Baseline AoAC and proteinuria were independently associated with eGFR decline. AoAC were independently determined by age, eGFR slope, and cardiomegaly. Conclusions . The coexistence of AoAC and cardiomegaly is associated with faster eGFR decline. AoAC is an independent determinant of renal outcomes in patients with CKD stages 3–5.